2020
DOI: 10.1038/s41598-020-78385-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiological screening of maternal periodontitis for predicting adverse pregnancy and neonatal outcomes

Abstract: It is well known that periodontitis, diagnosed mainly by periodontal probing, is associated with adverse pregnancy outcomes. However, periodontal probing is time-consuming, highly discomforting, inaccurate, and invasive. We aimed to assess whether periodontitis severity based on radiological staging in accordance with the 2017 new consensus classification was related to adverse pregnancy and neonatal outcomes. The medical records of 165 mothers who underwent panoramic radiography within 5 years before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…Heo JS. et al 14 Elaboraron su estudio obteniendo datos de registros de 165 mujeres durante su gestación, en los cuales se evidencio que 22 (13%) tenían periodontitis severa y 143 (86%) evidenciaban una periodontitis leve a moderada.…”
Section: Iiiresultadosunclassified
“…Heo JS. et al 14 Elaboraron su estudio obteniendo datos de registros de 165 mujeres durante su gestación, en los cuales se evidencio que 22 (13%) tenían periodontitis severa y 143 (86%) evidenciaban una periodontitis leve a moderada.…”
Section: Iiiresultadosunclassified
“…Likewise, another case‐control study in 2020 (60 cases, 120 controls) showed that the severity of periodontitis was significantly associated with low birth weight/preterm infants 17 . A retrospective cohort study (165 subjects, 22 severe periodontitis, 143 mild or moderate periodontitis) in 2020 found that the severity of periodontitis, based on radiological staging in accordance with the 2017 new consensus classification, was related to adverse pregnancy and neonatal outcomes, including uterine leiomyoma, chronic hypertension, preeclampsia, very preterm birth, extreme preterm birth, and small gestational age 18 . Another prospective cohort study (1394 participants) in 2020 also demonstrated that an increasing extent of gingival inflammation was associated with a nonsignificant increase in the risk of preterm birth 19 .…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…preterm birth, extreme preterm birth, and small gestational age. 18 Another prospective cohort study (1394 participants) in 2020 also demonstrated that an increasing extent of gingival inflammation was associated with a nonsignificant increase in the risk of preterm birth. 19 Nevertheless, anecdotal reports indicate that adverse pregnancy outcomes may be caused by even mild periodontal disease, such as pregnancy gingivitis, when combined with other underlying conditions, such as respiratory infections.…”
mentioning
confidence: 99%
“…Furthermore, studies have reported associations between periodontitis and adverse pregnancy outcomes like preterm deliveries (PD), low birth weight babies (LBW) and preterm low birth weight babies (PLBW). [10][11][12][13][14] Hence, good oral hygiene in pregnancy will help reduce the accumulation dental plaque and thus prevent the initiation of gingival inflammation and periodontal disease. 15 This study evaluated the perception of gingival bleeding in pregnancy as well as the oral hygiene practice, interdental cleaning and oral hygiene status of pregnant women attending the antenatal clinic of the Obstetrics and Gynaecology of the University of Port Harcourt Teaching Hospital, Port Harcourt, Rivers State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%